Granddaughter of the sun : a study of Euripides' Medea - Luschnig, C. A. E. (Mnemosyne, Supplements, 2007)
This book attempts to view Medea in a positive light: looking not just at her failed relationships, but also at her successful ones and commenting on her intellect rather than just her clever manipulations of men. It tries to see her (or her author, who brings Medea home to Athens), as something of a political hero. The work considers the multiple facets of Medea, as the ideal wife, as a loving mother, as a woman among women, and how Medea becomes the author of her own story. The author asks what Medea is in the last scene: a demon or one of us; how she relates to the city-state; why this heroic drama is presented through the voices of two slaves.